PENERAPAN MODEL DIRECT INSTRUCTION TERHADAP PENINGKATKAN KEMAMPUAN PASSING - M Zaena Sidik (Journal of Physical Education and Sport Science, 2021)
This study aims to improve futsal passing skills through the Direct Instriction method. This research is an experimental study which was carried out for approximately one month, with the intensity of meeting 3 times a week, a total of 2 weeks. Data were collected through pretest and posttest. The data were analyzed using SPSS version 23. The results showed that the direct instruction method was very suitable to be applied to class V students at SDN 2 Rajadanu because with direct instruction RPP participants could improve their passing skills. This can be seen from the increase in the results of the pretest at the time of the posttest. The conclusion is that direct instruction can improve the passing ability of class V students at SDN 2 Rajadanu